Exploring Sea Lice Vaccines against Early Stages of Infestation in Atlantic Salmon (Salmo salar) - Antonio Casuso; Valentina Valenzuela-Muñoz; Bárbara P. Benavente; Diego Valenzuela-Miranda; Cristian Gallardo-Escárate (Vaccines, 2022)
The sea louse Caligus rogercresseyi genome has opened the opportunity to apply the reverse vaccinology strategy for identifying antigens with potential effects on lice development and its application in sea lice control. This study aimed to explore the efficacy of three sea lice vaccines against the early stage of infestation, assessing the transcriptome modulation of immunized Atlantic salmon. Therein, three experimental groups of Salmo salar (Atlantic salmon) were vaccinated with the recombinant proteins: Peritrophin (prototype A), Cathepsin (prototype B), and the mix of them (prototype C), respectively. Sea lice infestation was evaluated during chalimus I-II, the early-infective stages attached at 7-days post infestation. In parallel, head kidney and skin tissue samples were taken for mRNA Illumina sequencing. Relative expression analyses of genes were conducted to identify immune responses, iron transport, and stress responses associated with the tested vaccines during the early stages of sea lice infection. The vaccine prototypes A, B, and C reduced the parasite burden by 24, 44, and 52% compared with the control group. In addition, the RNA-Seq analysis exhibited a prototype-dependent transcriptome modulation. The high expression differences were observed in genes associated with metal ion binding, molecular processes, and energy production. The findings suggest a balance between the host’s inflammatory response and metabolic process in vaccinated fish, increasing their transcriptional activity, which can alter the early host–parasite interactions. This study uncovers molecular responses produced by three vaccine prototypes at the early stages of infestation, providing new knowledge for sea lice control in the salmon aquaculture.